Clinical and hematological profile of sickle cell disease affected children in rural tertiary level hospital - Dr Varsha Shah; Dr Prasad Muley; Dr Chandani Choraria; Dr Pankaj Rana; Dr Devangi Kanara; Dr Abhishek Markana (Pediatric Review: International Journal of Pediatric Research, 2017)
Introduction: Sickle cell disease is commonly seen in rural population of western part of India. It is one of the common causes of recurrent hospitalization, morbidity and mortality in pediatric population. As there are limited studies addressing the pattern of sickle cell disease amongst pediatric population, this study was taken up to evaluate the clinicohematological profile of pediatric population with sickle cell disease in a rural tertiary care hospital in western part of India. Methods: This was a retrospective observational study. Data was retrieved from pediatric sickle cell clinic of the department. Data of children diagnosed with sickle cell disease from June 2013 to September 2016 was collected and analyzed to assess the hematological profile at the time of diagnosis and to find if there was any correlation between various hemoglobin variants and the hematological parameters. Results: About 173 patients were included in the study. Vasoocclusive crisis was the most common presentation (43.93 %) followed by generalized body ache joint pain (36.99 %) and acute febrile illness (26.39 %), while 45 (26.01%) patients presented with severe anemia. Hematological finding was suggestive of moderate anemia, low Mean corpuscular volume and low Mean hemoglobin concentration. Conclusion: At the time of diagnosis vasoocclusive crisis and generalized bodyache are the most common manifestations in pediatric population with sickle cell disease while hematological picture is suggestive of microcytic hypochromic anemia. There is a positive correlation between age at presentation and severity of anemia at the time of diagnosis.